2015
DOI: 10.1097/hjh.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Carotid flow velocity/diameter ratio is a predictor of cardiovascular events in hypertensive patients

Abstract: Lower carotid sFV/sAD was associated with MACEs in hypertensive patients independent of cardiovascular prediction models and carotid intima-media thickness. These findings suggest that this index may be a promising approach to identify hypertensive subjects at increased risk for future cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…However, another cross-sectional study reported that PSV is more associated with a cardiovascular event than EDV in hypertensive patients [15]. This study revealed that CIMT was more highly associated with PSV (r = -0.595) than with EDV (r = -0.232), and that CIMT was different between groups according to the level of PSV.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, another cross-sectional study reported that PSV is more associated with a cardiovascular event than EDV in hypertensive patients [15]. This study revealed that CIMT was more highly associated with PSV (r = -0.595) than with EDV (r = -0.232), and that CIMT was different between groups according to the level of PSV.…”
Section: Discussionmentioning
confidence: 66%
“…PSV and MS are independently associated with future CVD predicted by CIMT [12,13,15]. Moreover, PSV and MS are closely associated with traditional risk factors for CVD such as aging, body composition, blood pressure, and cardiorespiratory fitness [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two recently cross-sectional studies reported that low PSV and EDV were independently associated with future DVD7, 8 ) . The previous studies suggest that increase of PSV and EDV is associated with a potential prevention for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a followed-up study reported that low carotid artery flow velocity (i.e. peak-systolic velocity [PSV] and end-diastolic velocity [EDV]) is associated with CVD risk in hypertensive patients7 ) . Another study focusing on risk factor evolution and CVD development demonstrated that low PSV and EDV were independently associated with future CVD8 ) .…”
Section: Introductionmentioning
confidence: 99%